The Development of the Integrated Curriculum of the Buddhist Morals for Strengthening Social Adaptation of Vulnerable Youth - Radchaneeboon Neadpuckdee,; Natthakit Siriwatthanathakun,; Buncha Kietjarungphan,; Prachan Chachikul,; Phattharachai Uthaphan,; Prasong Promsri,; Khamphiraphap Kongsumruay, (Journal of Educational Issues, 2024)
The purposes of the study consequently were (1) to study background information needed in the development of a Buddhism curriculum in developing vulnerable youths’ social adaptation, (2) to develop a Buddhism curriculum in developing vulnerable youths’ social adaptation, and (3) to implement the Buddhism curriculum in developing vulnerable youths’ social adaptation. The study was divided into 3 phases including need analysis, curriculum development, and curriculum implementation. The participants were 50 stakeholders of vulnerable youth caregivers in phase 1, 5 experts in phase 2, and 100 vulnerable youths in phase 3. The instruments were an interview form, a curriculum evaluation form, an integrated curriculum of the Buddhist morals, and a pre-post test. The data were analyzed using content analysis, percentages, mean scores, standard deviation, and a paired sample t-test. The main findings could be summarized that using the integrated curriculum of the Buddhist morals was beneficial in strengthening the social adaptation of vulnerable youths. However, the developmental processes of the curriculum also demand the analysis of information regarding vulnerable youths, their environment, and potential Buddhism morals that could benefit their life skills. Students also need learning activities that could help them make a connection between religious morals and life situations.